Effect of yoga therapy on perceived stress, anxiety, quality of life, and heart rate variability in obese individuals - Buvanasvar Manoharan; Shetty Shivaprasad; Shetty Prashanth (Indian Journal of Integrative Medicine, 2021)
Background: Obesity is associated with stress, anxiety, and decreased quality of life an epidemic responsible for metabolic disorders. Yoga a holistic approach is aimed at restoring the abnormalities of body and mind physiology to normal thereby restoring health. The study aimed to assess the effect of yoga therapy on perceived stress, anxiety, quality of life, and heart rate variability in obese individuals. Materials and methods: 60 obese individuals were recruited for the study based on inclusion and exclusion criteria. The study population was divided into case group (n=30) received yoga therapy for 10 days with routine lifestyle and diet, and control group (n=30) followed routine lifestyle and diet Assessments were done on day 1 and day10 for both groups. Results: In the post-test assessments of the case group with the control group, there was a significant reduction in scores of perceived stress scale, and Hamilton anxiety rating scale, also reduction in mean HR, LF, LF/HF, and a significant increase in mean R-R variables of HRV in the case group. Conclusion: Ten days of yoga therapy in obese individuals had a positive effect on perceived stress, anxiety, quality of life, and heart rate variability, indicating parasympathetic dominance. Hence, yoga therapy acts in primary and secondary prevention of obesity-associated stress and anxiety symptoms.